Development of load balanced inverter - Mohaimeen, Najib (2012)
An inverteris an electrical device that can convert Direct Current (DC) into Altenating Current (AC) by using high frequency switching and power capabilities combined with complex control techniques. Inverter is a useful energy generation technology as it is one of the methods to practice green technology. It also can be used as an altenative energy source for rural area where the cost for grid connection is very expensive because of distance or geographical factor. A DC-AC inverter that is reliable for daily usage must be consistent with load connected and it should have an effiecient energy production. This includes all factors such as the pure sine wave output so that it can be used with sensitive electronic equipment. The output need to be steady with incresing load without voltage drop. The design of a load-balance inverter best to have a feedback system which can monitor the output produced as it can calibrate according to the changes onload. The inverter open loop design should be practice before the close loop implementation. A prototype of the DC-AC open loop inverter will be built based on this statement.Battery or solar panel can be use to provide the input DC fail. Filter will be integrated with the design so that it can have a smooth AC signal that reduced in harmonics. The conversion effectiveness and harmonic level of the inverter will be observed at the inverter output. The design of this inverter hopefully can be efficient and reliable enough to provide altenative energy generation for small scale in rural area or during mobility demand.